Alcohol imagery on popularly viewed television in the UK - Lyons, Ailsa; McNeill, Ann; Britton, John (Oxford University Press, 2013)
Background: Exposure to alcohol consumption and product imagery in films is associated with increased alcohol consumption among young people, but the extent to which exposure also occurs through television is not clear. We have measured the occurrence of alcohol imagery in prime-time broadcasting on UK free-to-air television channels. Methods: Occurrence of alcohol imagery (actual use, implied use, brand appearances or other reference to alcohol) was measured in all broadcasting on the five most popular UK television stations between 6 and 10 p.m. during 3 weeks in 2010, by 1-min interval coding. Results: Alcohol imagery occurred in over 40% of broadcasts, most commonly soap operas, feature films, sport and comedies, and was equally frequent before and after the 9 p.m. watershed. Brand appearances occurred in 21% of programmes, and over half of all sports programmes, a third of soap operas and comedies and a fifth of advertising/trailers. Three brands, Heineken, Budweiser and Carlsberg together accounted for ∼40% of all brand depictions. Conclusions: Young people are exposed to frequent alcohol imagery, including branding, in UK prime-time television. It is likely that this exposure has an important effect on alcohol consumption in young people.